A concise review of pharmacological and nonpharmacologic therapeutics in psychodermatology - Aditya K. Bubna (Journal of the Egyptian Women’s Dermatologic Society)
Often psychiatric co-morbidity has been observed in dermatology patients. Apart from regular dermatologic therapy employed in treating them; certain psychiatric drugs, along with other non-pharmacological measures, if combined in managing these patients, would certainly yield superior results. This comprehensive review throws light on various psychiatric drugs along with other adjuvant treatment modalities that could serve as a ready reckoner to skin specialists while encountering patients who apart from having cutaneous problems, also manifest with an associated psychological component that may need scrupulous evaluation in order to obtain a proper solution.